Improving educational and reproductive outcomes for adolescent mothers in South Africa: a cross-sectional analysis towards realizing policy goals - Jochim, J; Cluver, L; Sidloyi, L; Kelly, J; Ornellas, A; Mangqalaza, H; Coakley, C; Nogodua, C; Pillay, M; Nokama, B; George, G; Toska, E (Taylor and Francis, 2023)
Adolescent mothers face numerous challenges. This study aimed to address the operationalisation of the new South African national policy for young mothers by testing the associations of potential protective provisions with three policy goals: School return, grade promotion, and pregnancy/HIV prevention. Adolescent mothers aged 12–24 from rural and urban communities of South Africa’s Eastern Cape completed study questionnaires between 2017–2019. Using multivariate multi-level analysis, we simultaneously estimated associations between hypothesized provisions and protective variables and all policy-aligned goals. School return was associated with using formal childcare services, higher confidence and self-efficacy scores, and remaining in school throughout pregnancy. Grade promotion was associated with greater exposure to friendly and respectful health staff, using formal childcare services, higher confidence and self-efficacy scores, and remaining in school throughout pregnancy. Pregnancy/HIV prevention (condom use) was moderately associated with greater exposure to friendly and respectful health staff. There was evidence of synergies of provisions whereby a combination of protective characteristics showed larger positive effects than receipt of any single factor alone. This study provides essential evidence for operationalising South Africa’s new policy on the Prevention and Management of Learner Pregnancy in Schools, and points to implementation strategies that provide low-cost opportunities to promote educational and health outcomes for adolescent mothers.